The Connection between Hand Washing and Brushing Teeth - Ra-Ae Bak; Sun-Jung Shin; Hee-Jung Park; Jin-Young Jung; Hwa-Young Lee; Nam-Hee Kim (The Korean Society of Dental Hygiene Science, 2023)
Background: The purpose of this study was to identify the connection between handwashing and toothbrushing, focusing on eating habits, and to verify whether eating habits can be used as an action cue for forming health habits. Methods: This was a cross-sectional study using secondary data from the 2019 community health survey. The participants included 229,099 adults aged 19 years or older, representative of the South Korean people. We employed two dependent variables: one was washing hands, and the other was brushing teeth. Eating habits was a major independent variable. Socioeconomic variables, such as age, gender, income, occupation, economic activity, education, and residence were adjusted as confounders. Multivariate logistic regression was performed to calculate adjusted odds ratio and 95% confidence intervals. Results: Most of the participants had good health behaviors: those who wash their hands and brush their teeth were each approximately 80%. Our finding indicated that brushing teeth and washing hands can be connected with eating habits. After adjusting for confounders, it was found that people who wash their hands before meals (compared to those who did not wash their hands before meals) had a higher toothbrushing rate after meals (i.e., socioeconomic status) (Adjusted Odds Ratio: 2.0, Confidence Intervals: 1.9 to 2.1). Conclusion: Those who practice either washing hands before meals or brushing teeth after meals were found to have a connection between washing hands and brushing teeth based on the results of practicing other health behaviors. This implies that eating habits can be connected as a behavior cue to promote health habits, such as washing hands before meals and brushing teeth after meals.